Pengaruh Workplace Well-Being dan Kesehatan Mental terhadap Kinerja Karyawan pada PT Mega Hotel Lestari - Putri Sabrina Rafifah; Azhar Maulana; Erwin Gunawan (Yayasan Literasi Sains Indonesia, 2022)
Employees today can be defined as important assets for the company who play an active role in designing and solving problem strategies and have the responsibility to achieve company goals. To get good employee performance, companies need to pay attention to employee welfare and mental health. This study aims to determine the relationship between work-being and mental health on employee performance at PT Mega Hotel Lestari. The method used in this research is quantitative research. The population in this study were employees of PT Mega Hotel Lestari, taking samples using a purposive sampling technique with a total of 104 employees. This study used a data collection technique in the form of a questionnaire derived from a Likert scale. The data analysis technique used in this study is to use IBM SPSS 26.0 software using the Pearson Product Moment Correlation analysis method. The results of this study indicate that there is a positive and significant relationship between work welfare and mental health on employee performance at PT Mega Hotel Lestari as evidenced by a significance value of 0.000 and in the t test hypothesis the variable X1 has a Sig value of 0.031 and for X2 a Sig value of 0.000 which means that there is an effect of workplace well-being and mental health on employee performance.